A Wait-Free NCAS Library for Parallel Applications with Timing Constraints - Stellwag, Philippe; Scheler, Fabian; Krainz, Jakob; Schröder-Preikschat, Wolfgang (Proceedings of the 16th ACM Symposium on Principles and Practice of Parallel Programming 2011 (PPoPP 2011), 2011)
We introduce our major ideas of a wait-free, linearizable, and disjoint-access parallel NCAS library, called RTNCAS. It focuses the construction of wait-free data structure operations (DSO) in real-time circumstances. RTNCAS is able to conditionally swap multiple independent words (NCAS) in an atomic manner. It allows us, furthermore, to implement arbitrary DSO by means of their sequential specification. Copyright © 2011 ACM.
UnivIS-Import:2015-04-16:Pub.2011.tech.IMMD.IMMD4.awaitf
Keywords: pCtrl; wait freedom; disjoint-access parallelism; NCAS; real-time systems